Inventory modeling for spa business: a case study of phattaravadee zenity beauty and spa - Klumleantong, Mantana; Khokhajaikiat, Porntep (Engineering and Applied Science Research, 2013)
The objective of this research is to formulate the inventory model of massage oil (15 ml), which is the main material and has been highly used in the company. The amount of raw material order depends on the estimation of raw materials used by the owner. The overestimation of raw material consumption leads to increase ordering costs, holding costs and taxes. From the study of raw material consumption in the past, it was found that the usage rate of raw material was normal distribution. Therefore, the raw material model can be forecasted by Time series forecasting model and Artificial neural network model. Then the best forecasting model has the minimum of mean absolute deviation. The forecasting demand is applied to find the most economic order quantity, ordering period and the appropriate ordering frequency. From this study, the results showed that the average Inventory of raw material and the average total cost (ordering cost, holding cost and tax) during May to August 2011 was reduced to 50.45 percent and 23.60 percent respectively.